Analysis of Factors Affecting Adoption of Mobile Banking Application in Indonesia - Mufingatun Mufingatun; Budi Prijanto (Faculty of Economic and Business, 2020)
The development of information technology makes banking provide mobile banking service applications in Indonesia as an easy, convenient and fast service. However, there are still many customers who do not have a mobile banking account. In addition, the use of currency is still in demand by the soceity. Therefore, the purpose of this study is to determine the factors that influence consumer acceptance in the context of mobile banking applications. This study uses the Unified Theory of Acceptance and Use of Technology (UTAUT2) model which is modified by adding the variable perceived credibility and perceived self-efficacy. This research model was tested using 205 respondents from online surveys in the Jabodetabek, Indonesia. Data was analyzed using Partial Least Square (PLS). Performance expectancy, effort expectancy, social influence has a significant effect on behavioral intention. Performance expectancy is the factor that most influences the behavior intention. Behavioral intention, facilitating condition and habit has a significant effect on reuse behavior.